Kurva Sigmoid Pertumbuhan Tanaman Jagung pada Beberapa Tingkat Penanaman - Yuliana, Lia (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2024)
Corn plant growth is influenced not only by internal factors (genetic factors), but also by external factors. Climatic factors play a role in determining the growth and development of corn plants, including: water conditions, air temperature, air humidity, and CO2. In general, it can be said that the rate of plant growth increases with increasing temperature until the optimum temperature is reached. Corn has the same growth pattern, but the time interval between growth stages and the number of leaves that develop are different. Corn growth can be grouped into three stages, including: 1) germination phase; 2) vegetative growth phase; and 3) reproductive phase. This research aims to find out: 1) how much influence climate factors have on the growth and development of corn plants; and 2) corn plant growth patterns. This type of research was experimental with a Completely Randomized Design (CRD), with a single treatment factor, namely planting level C1 = 3 WAP, C2 = 4 WAP, C3 = 5 WAP, C4 = 6 WAP, and C5 = 7 WAP, which was repeated as many times as three repetitions. The data obtained was analyzed using Analysis of Variance and if there was a significant difference, it was continued with Duncan's Multiple Range Test at a confidence level of 95%. The conclusions obtained are: 1) good plant growth supported by appropriate genetic and climatic factors will increase biomass weight, 2) the plant growth rate shows exponential growth, and 3) at the beginning of growth assimilate is mostly used for vegetative growth, but entering The assimilate generative vase will experience a transition to a stronger sink part, namely flower formation.